A NEW URANYL CARBONATE SHEET IN THE CRYSTAL STRUCTURE OF FONTANITE, CA[(UO2)3(CO3)2O2](H2O)6 - Hughes K.A.; Burns P.C. (My University, 2003)
The structure of fontanite, Ca[(UO2)3(CO3)2O2](H2O)6, is monoclinic, space group P21/n, a = 6.968(3), b = 17.276(7), c = 15.377(6) Å , b = 90.064(6)8, V = 1851(1) Å 3 , Z = 4. The structure was solved by direct methods and refined on the basis of F 2 for all unique reflections using least-squares techniques to an agreement index (R1) of 9.9%. The structure contains two symmetrically distinct uranyl pentagonal bipyramids, one uranyl hexagonal bipyramid, and two CO3 triangles. The uranyl polyhedra form chains by sharing equatorial edges, and CO3 groups occur on either side of the chains, where they share equatorial edges of the uranyl hexagonal bipyramids. The CO3 groups share their third ligand with a uranyl pentagonal bipyramid of an adjacent chain, resulting in uranyl carbonate sheets of composition [(UO2)3(CO3)2O2]2 . The single symmetrically unique Ca 2+ cation is located between the sheets, and is coordinated by two O atoms of uranyl ions of adjacent sheets, and six H2O groups. The uranyl carbonate sheet in fontanite is novel, but is based upon the phosphuranylite anion topology that is the basis of uranyl phosphate, uranyl selen-ite, and uranyl sulfate sheets in a variety of minerals.
Keywords: MINERALOGY; CARBON; CRYSTALLOGRAPHY; fontanite